Micro-Raman spectroscopy analysis of dentin remineralization using eggshell derived nanohydroxyapatite combined with phytosphingosine. (May 2023) - Aruna Rani, S.V.; Rajkumar, K.; Saravana Karthikeyan, B.; Mahalaxmi, S.; Rajkumar, G.; Dhivya, V.
Abstract: The aim of this study was to assess the remineralization efficacy of chicken eggshell–derived nano-hydroxyapatite (CEnHAp) combined with phytosphingosine (PHS) on artificially induced dentinal lesions. PHS was commercially procured whereas CEnHAp was synthesized using microwave-irradiation method and characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), high-resolution scanning electron microscopy–energy-dispersive X-ray spectroscopy (HRSEM-EDX), and transmission electron microscopy (TEM). A total of 75 pre-demineralized coronal dentin specimens were randomly treated with one of the following test agents ( n = 15 each): artificial saliva (AS), casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), CEnHAp, PHS, and CEnHAp-PHS under pH cycling for 7, 14, and 28 days. Vickers microhardness indenter, HRSEM-EDX, and micro-Raman spectroscopy methods were used to assess the mineral changes in the treated dentin samples. Data were submitted to Kruskal–Wallis and Friedman's two-way analyses of variance ( p < 0.05). HRSEM and TEM analysis depicted irregular spherical structure of the prepared CEnHAp with a particle size of 20–50 nm. The EDX analysis confirmed the presence of Ca, P, Na and Mg ions. The XRD pattern showed the characteristic crystalline peaks for hydroxyapatite and calcium carbonate that are present in the prepared CEnHAp. Dentin treated with CEnHAp-PHS revealed highest microhardness values along with complete tubular occlusion compared to other groups at all test time intervals ( p < 0.05). Specimens treated with CEnHAp showed increased remineralization than those treated with CPP-ACP followed by PHS and AS groups. The intensity of mineral peaks, as observed in the EDX and micro-Raman spectra, confirmed these findings. Further, the molecular conformation of the collagen's polypeptide chains, and amide-I and CH2 peaks attained peak intensities in dentin treated with CEnHAp–PHS and PHS whereas other groups revealed poor stability of collagen bands. Microhardness, surface topography, and micro-Raman spectroscopy analyses revealed that dentin treated with CEnHAp–PHS have an improved collagen structure and stability as well as highest mineralization and crystallinity. Graphical abstract: Image 1 Highlights: Preserving the demineralized dentin matrix plays a pivotal role in today's restorative dentistry. Phytosphingosine (PHS) may serve as a promising biomaterial to strengthen dentin and improve stability. PHS along with egg shell derived nano-hydroxyapatite can be effectively employed in treating demineralized dentin lesions.